Bioeconomics of reindeer husbandry in Fennoscandia - Pekkarinen, Antti Juhani; Kumpula, Jouko; Holand, Øystein; Åhman, Birgitta; Tahvonen, Olli (2023)
Reindeer husbandry is an important economic activity in the Arctic. Growth rate and productivity of reindeer populations depend on pasture conditions, but herders’ decisions are also influenced by economic factors. Thus, to understand the reindeer husbandry system, an economic–ecological analysis is needed. Bioeconomic models provide a suitable approach for studying economic–ecological systems. Reindeer populations, as well as their pastures, can be viewed as biological resources utilized in reindeer husbandry. To analyse optimal herd structure and slaughter strategy, structured models are needed. This chapter employs a bioeconomic, age- and sex-structured reindeer-pasture model to study economically sustainable adaptation and management under different conditions. The model is run for three hypothetical herding districts, which represent the typical variation in conditions between and within Fennoscandian countries. The chapter analyses how these differences in ecological and economic conditions affect the model solutions and explores optimal herd sizes, slaughter and feeding strategies, lichen biomass dynamics and net revenues under different conditions. Finally, the chapter discusses and compares economic incentives, pasture conditions and government regulation in Nordic countries in the light of the model analysis. Peer reviewed